Constructions of absentee fatherhood amongst black South African men - Matee, Hopolang Nnete Moipone (My University, 2017)
This study aimed to explore constructions of absent fatherhood amongst Black South African men, as well as the factors that contribute to these constructions. Individual semi-structured interviews were conducted with five Black men between the ages of 25-50, who had not had contact with their children since infancy. Absent fatherhood in South Africa has been highlighted in the literature, however, most studies have been conducted from the perspectives of the mother and children, with a focus most often on the effects of absent fatherhood on the child. It was thus significant to explore absent fatherhood from the fathers’ perspectives, in order to understand their experiences. The interviews were analysed using Braun and Clarke’s (2006) qualitative thematic analysis. Constructions of fatherhood included notions of father as provider, symbol of strength and source of wisdom and guidance. Fathers were seen as powerful figures, connected to culture and tradition. Given that all the participants had experienced their own fathers as absent, it was significant to note maternal influences on their constructions of fatherhood. Constructions of absentee fatherhood included notions of powerlessness due to financial and cultural expectations and a lack of control over decision making. Absent fathers were also frequently constructed as victims. A number of historical and current contextual influences were identified in absent fatherhood, such as unplanned pregnancies and a lack of readiness for fatherhood. Many of the participants reported negative childhood experiences with their own fathers, racial and socio-economic influences on fatherhood were identified. Powerlessness with regards to the Justice system was highlighted, as well as the influence of maternal gate-keeping. It was concluded that South Africa’s traumatic history is implicated in the issue of often intergenerationally transmitted absent fatherhood amongst Black men. The maternal, familial and cultural structures that have developed to accommodate absent fatherhood may in fact be perpetuating the problem Black men appear to be feeling too powerless to take on a role that they perceive to be powerful and may need more facilitation when it comes to transitioning into fatherhood. It may be worthwhile to reconsider cultural and other socio-economic structures that can assist with contextual issues that black South African men are faced with.
A research project submitted in partial fulfilment of the requirements for the degree of BA Masters in Psychology in the faculty of Humanities, University of the Witwatersrand, Johannesburg, November 2016.
Keywords: Absentee fathers--South Africa--Psychological aspects; Fatherhood--South Africa